Biomedical Consequences of Alcohol Use Disorders in the HIV-Infected Host - E. Molina, Patricia; J. Bagby, Gregory; Nelson, Steve (Current HIV Research, 2014)
Alcohol abuse is the most common and costly form of drug abuse in the United States. It is well known that alcohol abuse contributes to risky behaviors associated with greater incidence of human immunodeficiency virus (HIV) infections. As HIV has become a more chronic disease since the introduction of antiretroviral therapy, it is expected that alcohol use disorders will have an adverse effect on the health of HIV-infected patients. The biomedical consequences of acute and chronic alcohol abuse are multisystemic. Based on what is currently known of the comorbid and pathophysiological conditions resulting from HIV infection in people with alcohol use disorders, chronic alcohol abuse appears to alter the virus infectivity, the immune response of the host, and the progression of disease and tissue injury, with specific impact on disease progression. The combined insult of alcohol abuse and HIV affects organ systems, including the central nervous system, the immune system, the liver, heart, and lungs, and the musculoskeletal system. Here we outline the major pathological consequences of alcohol abuse in the HIV-infected individual, emphasizing its impact on immunomodulation, erosion of lean body mass associated with AIDS wasting, and lipodystrophy. We conclude that interventions focused on reducing or avoiding alcohol abuse are likely to be important in decreasing morbidity and improving outcomes in people living with HIV/AIDS.
Keywords: SIV